Outcomes After Salter–Harris II Distal Tibia Fractures in Children - Robert Pearce; Alexander Markes; Toshali Katyal; Jeremy Siu; Ishaan Swarup (Children)
Background/Objectives: Salter–Harris II (SH-II) distal tibia fractures are the most common physeal ankle fractures in children; however, indications for surgical management remain controversial, and patient-reported outcomes for different management strategies are unknown. The purpose of the current study is to compare differences in clinical and patient-reported outcomes following operative and non-operative management of this injury. Methods: We performed a retrospective cohort study of pediatric patients who were treated at a single institution for SH-II distal tibia fractures between 2013 and 2020. Variables included age, gender, operative versus non-operative treatment, and premature physeal closure (PPC). Patients were also contacted for patient-reported outcome scores (PROs), which included the visual analog scale foot and ankle (VAS-FA) and the PROMIS pediatric mobility instrument obtained at a minimum of 2 years post-injury. Results: Demographic and clinical information was obtained for 46 patients. Our cohort was 52% male with mean age of 11.9 years at injury. At 6 months, the rate of PPC in our cohort was 25%, with no differences between operative and non-operative patients (29% vs. 24%, p = 0.80). A total of 15 of the 46 patients provided PROs, with an average follow-up time of 5.1 years (range: 2.9–9.1). VAS-FA and PROMIS pediatric mobility scores were similar between operative and non-operative patients. Conclusions: This pilot study suggests no differences in PROs following operative and non-operative management for SH-II distal tibia fractures; however, future studies with larger cohort sizes and longer follow-up times are needed to further examine these outcomes.